Global burden of disease and risk factors - Lopez, Alan D.; Disease Control Priorities Project (New York, NY : Oxford University Press ; Washington, DC : World Bank, 2006)
This volume is a single up-to-date source on the entire global epidemiology of diseases, injuries and risk factors with a comprehensive statement of methods and a complete presentation of results. It includes a refined methods to assess data, ensure epidemiological consistency, and summarize the disease burden. 'Global Burden of Disease and Risk Factors' examines the comparative importance of diseases, injuries, and risk factors; it incorporates a range of new data sources to develop consistent estimates of incidence, prevalence, severity and duration, and mortality for 136 major diseases and injuries.Drawing from more than 8,500 data sources that include epidemiological studies, disease registers, and notifications systems, 'Global Burden of Disease and Risk Factors' incorporates informationfrom more than 10,000 datasets relating to population health and mortality, representing one of the largest syntheses of global information on population health to date.
"Disease Control Priorities Project"--Cover.
Includes bibliographical references and index.
rpm 27/09/2016
Loans
Keywords: World health; Diseases; Diseases -- Risk Factors .; Health risk assessment; Health Status Indicators; Global Health; Risk Factors